Pelatihan Pendidikan Karakter bagi Pelatih Pencak Silat Persaudaraan Setia Hati Terate “PSHT” Cabang Pamekasan - Fredy Yunanto; Ria Kasanova; Syaiful Syaiful; Mohammad Rudiyanto; Syaiful Anam; Hasbullah Hasbullah (Batara Wisnu : Indonesian Journal of Community Services, 2022)
This training course aims to increase the knowledge of the pencak silat trainer of the Setia Hati Terate "PSHT" about the importance of character building in students. Since adolescence, students need to be equipped to shape their personality, because adolescence is a golden age in human life. There are four values ??learned in this training course from these character education values, namely, (1) love of truth (2) responsibility, legal discipline and independence, (3) reliability and (4) respect and courtesy. The participants of this training course were attended by 15 Pencak Silat trainers from the Pamekasan city branch. Based on the results of the assessment, it is known that almost 90% of the trainers understand the material given